2009
DOI: 10.1136/bjo.2007.137265
|View full text |Cite
|
Sign up to set email alerts
|

Euthyroid and primarily hypothyroid patients develop milder and significantly more asymmetrical Graves ophthalmopathy

Abstract: Background and aims: Retrospective, observational study to compare clinical symptoms and TSH-receptor antibodies (TRAb) in Graves ophthalmopathy (GO) in euthyroid and primarily hypothyroid patients to those in hyperthyroid patients. Methods: Clinical symptoms (NOSPECS (severity) and CAS (activity) score), prevalence and levels of thyroid specific antibodies and the course of the disease were evaluated in 143 primarily hyperthyroid, 28 primarily euthyroid and 11 primarily hypothyroid patients with GO. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
5
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 22 publications
(25 reference statements)
7
93
5
13
Order By: Relevance
“…25 However, hypothyroidism as primary thyroid dysfunction associated with TED was reported from 0.2 to 8.6% of patients with TED, most of them had autoimmune type of hypothyroidism (Hashimoto's thyroiditis). 1,3,4,9,10,26,27 Although autoantibodies were not checked for all the patients because of unavailability, our endocrinologists believed that Hashimoto's thyroiditis was the main cause of hypothyroidism in this series. Our result of 7.5% Ho-TED is more than what has previously been reported.…”
Section: Resultsmentioning
confidence: 93%
“…25 However, hypothyroidism as primary thyroid dysfunction associated with TED was reported from 0.2 to 8.6% of patients with TED, most of them had autoimmune type of hypothyroidism (Hashimoto's thyroiditis). 1,3,4,9,10,26,27 Although autoantibodies were not checked for all the patients because of unavailability, our endocrinologists believed that Hashimoto's thyroiditis was the main cause of hypothyroidism in this series. Our result of 7.5% Ho-TED is more than what has previously been reported.…”
Section: Resultsmentioning
confidence: 93%
“…Our results also support a previous report that in Asians, TSI measurement is a more sensitive marker of euthyroid TAO than TBII measurements. 10 Among the three patients in whom TBII/TSI assays were negative, the patient presenting with diplopia and unilateral proptosis did not show typical symptoms or signs of orbital myositis such as acute pain exacerbated by eye movement. The CT scan revealed right inferior and medical rectus enlargement without anterior tendon involvement.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Because most cases involving euthyroid TAO showed no thyroid abnormalities except testing positive for thyroidstimulating hormone receptor antibodies (TRAbs), 7,9 the clinical significance of TRAb as a criterion in the diagnosis of euthyroid TAO has been suggested. 3,6 Recently, Eckstein et al 10 reported that the TRAb titer was low in euthryoid and hypothyroid patients, suggesting that a more sensitive assay technique was necessary to utilize the TRAb assay for diagnosis of euthyroid/hypothyroid TAO. The TRAb assay used in this report was the thyrotropin-binding inhibitor immunoglobulin (TBII) assay, which cannot discriminate between thyroid-blocking immunoglobulin and thyroidstimulating immunoglobulin (TSI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of GO in euthyroid and primarily hypothyroid patients ranges between 1.6% and 8.6% [1]. Orbitopathy in hypothyroid/euthyroid patients present with less soft tissue involvement, more asymmetrical disease and clinically less marked symptoms than in primarily hyperthyroid patients [1].…”
Section: Introductionmentioning
confidence: 99%